The Relationship between Electricity Consumption, Price of Oils, and Gross Domestic Product in the Gulf Cooperation Council Countries - Benlaria, Houcine; Almawishir, Naeimah Fahad S. (International Journal of Energy Economics and Policy, 2024)
The research aimed to evaluate the impact of electricity consumption and oil prices on the GDP of GCC countries. The oil industry is the backbone of economies in these countries, accounting for a significant portion of GDP. The variations and volatility in petroleum prices significantly affect GCC countries’ GDP. Moreover, these countries have also increased the usage of electricity. A substantial increase in the demand for electricity impacts the economic development of GCC countries. The study has considered a quantitative method using secondary data to address the research objective. The data for electricity consumption, energy use, and oil prices were obtained from the World Development Indicators website from 2010 to 2021. The countries include Bahrain, Oman, Qatar, the United Arab Emirates (UAE), Saudi Arabia, and Kuwait. The data obtained were empirically analyzed using the system-GMM approach as it was identified to be a more robust estimation model controlling for issues such as autocorrelation and endogeneity. The results obtained from the system-GMM indicated that electricity consumption and oil prices positively impact the GDP of GCC countries. At the same time, energy use hurts the GDP. Therefore, the research findings imply that electricity consumption and oil prices significantly contribute to the growth of the GCC countries.